Arahan Pengembangan Perkebunan Teh (Camellia Sinensis (L.) O. Kuntze) Rakyat di Kabupaten Tasikmalaya - Agung Lukman; Atang Sutandi; Khursatul Munibah (P4W LPPM IPB, 2017)
Tea is a common plantation commodity cultivated by the community and developed by Tasikmalaya government.According to Tasikmalaya regency regional planning, tea has been established as one of commodities at but it doesn’t have further policy dvelopment. The aims of this study are (1) to identify smallholdertea plantation; (2) to analyze land suitability and to identify potential development areas for tea crop; (3) to analyze the feasibility of tea farming; (4) to determine policy development of smallholdertea plantation. Satellite image interpretation was used toidentify smallholdertea plantation. A method of matching criteria was used to analyze land suitability for tea crop and the potential development areas weredetermined by using descriptive analytic. SWOT analysis was used to determine the policy development of smallholdertea plantation. The results showed that tea smallholder plantation was about 6,956hectares. The suitable land for tea crop was about 55,310 hectares and its potential development area was about 14,979 hectares. Smallholdertea plantations was feasible to be developed with R/C ratio 1.73. In order to support the development of smallholdertea plantation some recommendations aresuggested consisting of (1) the government should encourage the development of tea processing industry to increase farmers income; 2) smallholdertea plantation should be extended considering land availability and suitability; 3) the role of tea smallholder farmer groups and privates plantation should be enhanced to develop tea plantation as a strategic commodity in Tasikmalaya Regency.